Automated marking system for laboratory experiments - Yeow, Matthew Ying Kang (Nanyang Technological University, 2024)
Work-related stress in Singapore is a major issue that needs to be addressed. In the context of education, relieving the marking workload of our educators would be one way to help resolve the situation. In this report, I will explain how my project, Automated Marking System for Laboratory Experiments, is executed and how this project would help reduce the amount of marking for our educators.